The effectiveness of one "physical education minute" during lessons to develop concentration in 8- to 10-year-old schoolchildren - Georgiy Polevoy; Georgiy Polevoy; Florin Cazan; Johnny Padulo; Luca Paolo Ardigò (Frontiers Media S.A., 2023)
The demands of the school day, which includes multiple lessons, require sustained attention from students; this can be challenging, especially for young children. Concentration of attention is a critical cognitive function that impacts learning. This study involved 129 healthy schoolchildren aged 8-10 years (spanning grades 2 and 3) from a regular secondary school in Kirov, Russian Federation. A "physical education minute" (PEM), consisting of various physical exercises, was introduced during the middle of a regular lesson for the experimental group (EG), while the control group (CG) continued with their regular studies. Concentration and attention were assessed before and after the PEM using the Bourdon test. The Bourdon test results indicated a significant decrease in concentration during the lesson for the CG (p < 0.001), while the EG exhibited significant improvement in concentration after the PEM (p < 0.001). The effect size was large, demonstrating a substantial impact of this break for physical activity on concentration. It can be concluded that implementing a set of exercises in the form of a PEM in the middle of a lesson significantly improves concentration among students aged 8-10. This study underscores the effectiveness of integrating short breaks for physical activity into the daily classroom routine, ultimately benefiting students' attention, learning, and overall educational experience. Further research could explore additional factors affecting concentration and the long-term effects of the PEM on cognitive development.